Scientific Learning Through The Edu Eco Approach As An Alternative Improving Student Knowledge And Skills - Oktaffi Arinna Manasikana, (Jurnal Serambi Ilmu, 2024)
One of the real scientific learning is done through learning about environmental concepts and their utilization, namely edu eco. The objectives of this study are: (1) Provide student knowledge about real learning of the concept of herbal hydroponics by utilizing household waste (eco edu); (2) Provide student skills about processing organic waste as plant nutrients; (3) Provide student skills about hydroponic herbal plant cultivation. This type of research is descriptive through a qualitative approach. Data collection of learning knowledge through objective tests while for learning skills data through questionnaires. The subjects of this study were science education students of Hasyim Asy'ari Tebuireng University Jombang who were taking the Population and Environmental Education (PKLH) course. The results showed: (1) There is an effect of providing knowledge about real learning of the concept of herbal hydroponics by utilizing household waste through increasing the mean value of the pre test (67.4) and post test (83.6); (2) From the questionnaire results, the skills of making plant nutrients from organic waste obtained a mean value of 85.6; and herbal hydroponic skills mean value 84.3 (3) Student response to edueco 87% of students strongly agree.